L'aile dite « des prélats » au château de Grignan (Drôme) 1684-1689 - Christian Trézin (In Situ)
The "prelates" wing of the castle of Grignan was built from 1684 to 1689. It was supposed to be a requalification and a renewal of a heterogeneous area erected between 12th to 17th century. Sponsored by the bishop of Carcassonne and the archbishop of Arles, brothers of the count of Grignan, no architect was involved in its design. It was built in two successive phases reflecting distinct conceptions and accordingly its architctural harmonization was made difficult and remained unfulfilled. If the Carcassonne building reflects the traditional savoir faire of the building contractor Florent Loiseleur, Arles's was deeply close to the recent works of Jules Hardouin-Mansart's agency whom the master builder Jacque Jaquet, said Beaufleury, had most probably to be inspired of. This construction is an example of the way amateur architects used to work in the conservative circle of provençal nobility.